2022
DOI: 10.3390/su14042405
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Uneven Flow Wastewater Distribution on the Technological Efficiency of a Sequencing Batch Reactor

Abstract: Variability in the load of pollutants significantly influences the efficiency of activated sludge technology in municipal wastewater treatment plants, both in terms of flow systems and in sequencing batch reactors (SBR). Diversified inflow of wastewater to the treatment plant has a significant impact on the technological efficiency of sequencing batch reactors. Additionally, this problem is intensified in technological systems in which there is no storage tank for raw wastewater. It is assumed, however, that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…However, the variation trend of the TN removal was almost the same for the NH 3 -N removal due to its proportion of concentration value. Initially, there were rapid processes for the nitrogen removal through the physicochemical adsorption and cation exchange capacity [16,17]. However, during the later stable period, the nitrification and denitrification in the aerobic PLs and anaerobic SMBs were the primary drivers for the biotransformation of NH 3 -N and NO 3 − -N [1,26], respectively.…”
Section: Nitrogen Removalmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the variation trend of the TN removal was almost the same for the NH 3 -N removal due to its proportion of concentration value. Initially, there were rapid processes for the nitrogen removal through the physicochemical adsorption and cation exchange capacity [16,17]. However, during the later stable period, the nitrification and denitrification in the aerobic PLs and anaerobic SMBs were the primary drivers for the biotransformation of NH 3 -N and NO 3 − -N [1,26], respectively.…”
Section: Nitrogen Removalmentioning
confidence: 99%
“…It has been applied over the world and is now widely attracting attention as well [14,15]. There are two types of modules that were installed in the MSL system (permeable layer (PL), soil mixture block (SMB)) to significantly facilitate the aerobic and anaerobic conditions, respectively [16]. Moreover, the MSL system has various advantageous features, such as an intensive space utilization, a net zero energy consumption, smooth flow, easy maintenance, good aesthetic, and no odor [9,15].…”
Section: Introductionmentioning
confidence: 99%
“…Also, AGS is not usually efficient for complete N removal, and other biological processes are needed. Other studies have shown that wastewater variability does not always ensure COD, N, and P removal, even using dedicated N and P biological removal systems [ 13 , 14 ]. Nevertheless, these systems do not consider resource recovery within a circular economy concept in their design or operation.…”
Section: Introductionmentioning
confidence: 99%
“…As the name implies, the concept of SBR technology is to treat wastewater using the activated sludge, where the processes of biological treatment and separation occur in the same tank in a sequential mode. SBRs are most popular as solutions in urban areas, as well as in rural areas [32][33][34][35]. Examples of malfunctions include failures of aeration systems resulting in the disruption of aerobic conditions, or failures of mixing systems necessary for proper processes under hypoxic and anaerobic conditions.…”
Section: Introductionmentioning
confidence: 99%